FETURES OF PROTECTIVE STRUCTURE DESIGN DUAL PURPOSE - Слободяник, Ганна; Куємжи, Павло (SWorldJournal, 2024)
Currently, the design and construction of defensive structures is extremely relevant in the conditions of martial law. An analysis of the main provisions of DBN V.2.2-5:2023 "Protective structures of civil protection" was carried out in the section of con